Handbook of numerical analysis. - Ciarlet, Philippe G. (North-Holland, 2009)
Mathematical Finance is a prolific scientific domain in which there exists a particular characteristic of developing both advanced theories and practical techniques simultaneously. Mathematical Modelling and Numerical Methods in Finance addresses the three most importants aspects in the field: mathematical models, computational methods, and applications and provides a solid overview of major new ideas and results in the three domains. . Coverage of all aspects of quantitative finance including models, computational methods and applications . Provides an overview of new ideas and results . Contributors are leaders of the field.